Antileishmanial activity of 1,3,4-thiadiazolium-2-aminide in mice infected with Leishmania amazonensis - Rodrigues, Raquel F. (2009)
Fundação Oswaldo Cruz. Instituto Oswaldo Cruz. Laboratório de Bioquímica de Tripanossomatídeos. Rio de Janeiro, RJ, Brasil.